Digital resilience in Chinese adolescents: a portrayal of the current condition, influencing factors, and improvement strategies - Qi, Chunlin; Yang, Nanchang (Frontiers in Psychiatry, 2024)
This study investigates the significance and effects of digital resilience in adolescent education. Adolescents' living and learning environments have changed considerably due to the widespread adoption of digital technology in education. Enhancing adolescents' digital resilience is essential to helping them embrace technology correctly. However, established needs are scarcer when evaluating digital resilience in adolescents. As a result, this study aimed to create and evaluate a digital resilience questionnaire for Chinese adolescents based on the theoretical framework of digital resilience. This study adopted a mixed research methodology, combining quantitative and qualitative data collection and analysis. A questionnaire was administered to 12,208 adolescents from 10 high schools and 16 middle schools over six months (January to June 2023), and in-depth interviews were conducted with 10 of these adolescents. The findings suggest that Chinese adolescents' digital resilience levels are slightly above average (M = 3.5038 > 3.5), but there is still room for improvement, especially in active learning. In addition, some factors affecting adolescents' digital resilience were identified, such as gender, family residence, being an only child, grade level, number of digital devices used weekly, and the length of Internet surfing every day. Three recommendations for improving adolescent digital resilience are proposed based on the above information. This study contributes to the knowledge of digital resilience and improves its practical applicability.